Data-Driven Insights for Agricultural Extension Services in Rajasthan: A Study of Kisan Call Center Queries (Indian Journal of Extension Education, 2024)
Adopting a demand-driven approach in an ever-evolving agricultural domain is imperative for the effectiveness of agricultural extension services, particularly in the state of Rajasthan, India. The paper comprehensively analyses the vast dataset comprising over four million farmer query calls to the Kisan Call Center in Rajasthan from January 2009 to August 2023. These meticulously preprocessed call records serve as a crucial bridge between the agricultural community and support services, providing invaluable insights into the challenges and needs of Rajasthan’s farmers. Our analysis examines temporal trends in farmer query calls, revealing year-wise and month-to-month insights, including peak call activity periods. The district-wise analysis aids targeted interventions. Understanding call distribution across diverse landscapes. Categorising calls by crop and query type offers insights into distinct farmer challenges, informing tailored policies and support programs. In conclusion, this research underscores the paramount importance of harnessing data driven insights to enhance agricultural support systems in Rajasthan. By doing so, we can ensure the long-term sustainability and prosperity of the farming community, thus contributing to the overall well-being of the state’s agriculture sector. The research is useful for informing evidence-based policy decisions and tailored support services to enhance agricultural productivity and sustainability in Rajasthan.